RBPB: Regularization-Based Pattern Balancing Method for Event Extraction - Sha, Lei; Liu, Jing; Lin, Chin-Yew; Li, Sujian; Chang, Baobao; Sui, Zhifang (Proceedings of the 54th Annual Meeting of the Association for Computational Linguistics (ACL), 2016)
Event extraction is a particularly challenging information extraction task, which intends to identify and classify event triggers and arguments from raw text. In recent works, when determining event types (trigger classification), most of the works are either pattern-only or feature-only. However, although patterns cannot cover all representations of an event, it is still a very important feature. In addition, when identifying and classifying arguments, previous works consider each candidate argument separately while ignoring the relationship between arguments. This paper proposes a Regularization-Based Pattern Balancing Method (RBPB). Inspired by the progress in representation learning, we use trigger embedding, sentence-level embedding and pattern features together as our features for trigger classification so that the effect of patterns and other useful features can be balanced. In addition, RBPB uses a regularization method to take advantage of the relationship between arguments. Experiments show that we achieve results better than current state-of-art equivalents.